(untitled) (Actualizaciones en Sida e Infectología, 2022)
The COVID-19 pandemic produced, among many other consequences, a marked increase in the frequency of healthcare-associated infections (HAIs), just as antimicrobial resistance (AMR) has accelerated to unprecedented levels (1, 2). This problem, of global significance, has a strong impact on Argentina, where some estimates indicate that AMR rates reached during 2021 seemed only possible by 2029, according to previous speculations (2). On the other hand, a recent Argentine study, carried out on 466 strains of carbapenem-resistant gram-negative bacilli isolated from blood cultures (K. pneumoniae 53%, A. baumanii 25%), showed a mortality associated with the episodes of 50%. Of these bacteremias, 25% had received inadequate initial empirical treatment, and metallo-β-lactamases were shown to emerge as a worrisome resistance mechanism (3). This shows the magnitude of the problem, its unusual growth and the consequences on human health, in terms of morbidity and mortality. In turn, this growth implies an increase in the use of high-cost antimicrobials, days of hospitalization and complications that result in the economic impact that the AMR phenomenon has on the world. A few weeks ago, Argentina passed Law 27,680 on the Prevention and Control of Antimicrobial Resistance (4). This law, the first in the field, fills a gap that our country had with its public health. The closest regulatory precedent that can be found with respect to the prescription and dispensing of antibiotics dates back to Ministerial Resolution 3835 of 1969. More than 50 years have passed since then. The federal organization of our country allowed the regulation to be unevenly applied and eventually the controls faded away in many jurisdictions. On the other hand, in the same five decades, society has undergone enormous changes, its commercial processes have been modified, advertising has entered the pharmaceutical industry with great power, and at the same time -as we mentioned before- the problem of AMR has become pressing and of a complexity that was not present until the end of the 1990s. In 2014, the Ministry of Health of Argentina, together with other agencies, institutions and scientific societies such as SADI, initiated a national strategy for the control of AMR (5). Similarly, there were local regulatory gestures in some provinces and municipalities, as well as particular efforts such as those linked to livestock farming and the use of some antimicrobials in their practices. These actions are coordinated by the National Commission Against Antimicrobial Resistance (CONACRA), which tries to carry out the program beyond temporary political ups and downs and changing policies. Law 27,680 establishes a regulatory framework for the following situations: sale of systemic antimicrobials under filed prescription, ban on the advertising of antimicrobial-containing medicines, adequacy of drug presentations to the usual dosages and treatment times, elimination of the use of antimicrobials as growth promoters in livestock farming, strengthening antimicrobial resistance surveillance at the national level, promotion on the implementation of infection control programs in all healthcare institutions, with surveillance of HAIs, awareness raising, advocacy and education on the impact of HAIs and AMR on human, animal and environmental health, promotion of research and development of new drugs with antimicrobial activity, as well as of rapid and efficient methods for microbiological diagnostics. In its Article 2, the law declares "the prevention and control of antimicrobial resistance of national public interest," thus providing a national framework that limits the possibility for provincial jurisdictions to deviate from its compliance. It was sanctioned through a parliamentary process almost unanimously in both Houses, after several years of joint work by legislators, organizations such as SENASA[1], Anlis-Malbrán[2] and INE[3], and scientific associations such as SADI, ADECI[4] and SATI[5]. The law is not enough, but it is necessary. A future of regulation and implementation lies ahead, laborious and arduous, in which the implementation of each point will find its way. We must work on education at all levels as a fundamental instrument of change: the problem must be addressed from the initial levels of formal education and must be included in the agendas of society as a whole, just as problems such as the energy crisis, global warming or ecological catastrophes are recognized as central issues for a future that has long since arrived. It is necessary to point out that both infection prevention and control practices and the responsible use of antimicrobials could slow the emergence and spread of AMR and, therefore, save lives. In this sense, we in hospitals should focus on improving our hand hygiene practices, hospital hygiene and optimizing the use of antimicrobials, measures that according to a report by the Overseas Cooperative Development Council (OCDC) would reduce 85% of the burden of antimicrobial resistance (6). Towards the end of the 1930s, at a conference in Buenos Aires, Ortega y Gasset pronounced his famous phrase "Argentines, get to it!" which would later appear in his book "Meditación del pueblo joven" (Meditation of the Young People). The philosopher encouraged Argentines to "leave aside previous personal questions, suspicions, narcissism..." and challenged us: "Don’t you presume what a magnificent leap this country will take the day its men resolve once and for all, bravely, to face things, care about them and deal with them directly and without further ado...". In times of crisis, the leadership often prioritizes its efforts to deal with short-term situations. On this occasion, the leadership focused on a central issue that exceeds the short term and its efforts took the form of a law that we had demanded and now celebrate. We should rejoice, just as we should be aware that the task has just begun. [1] Servicio Nacional de Sanidad y Calidad Agroalimentaria National - Agrifood Health and Quality Service, [2] Administración Nacional de Laboratorios e Insititutos de Salud - National Administration of Laboratories and Health Institutes. [3] Instituto Nacional de Epidemiología - National Institute of Epidemiology [4] Asociación Argentina de Enfermeros en Control de Infecciones - Argentine Association of Infection Control Nurses [5] Sociedad Argentina de Terapia Intensiva - Argentine Society of Intensive Care